INFORMASI KEUANGAN DAN NON KEUANGAN TERHADAP RETURN SAHAM DI PASAR PERDANA - Lestari, Yona Octiani (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2011)
Financial statement and Non Financial statement need investor at initial market (IPO). The underpricing fenomenal in Initial Public Offering (IPO) is investor get positif return in initial market. The one is caused by asimetry informations in initial market. Investor need some informations, but the informations was getting prospectus informations only. And this research explain to test aboute financial statement and non financial statement to return in initial public offering. The sampling of research were 58 manufacturing and non manufacturing were listing in Bursa Efek Indonesia (Idx) at 2002-2004. Sampling method with purposive sampling. The ones must underpricing and prospectus statement full disclosure. The analyse used multiple regretions. To find relations of auditor reputations, guarantor reputation, old age company, equity percentage which on the market, ROA, leverage, industrial sector with initial return. Result of analysis indicate that there is two variable having an effect on significance to initial return that is emission guarantor reputation and auditor reputation. Assess significance T for the auditor reputation is 0.037 meaning significance at 5%. While result of test correlation indicate that emission guarantor reputation variable can explain initial return equal to 0.200 or equal to 20% positive to initial return. This result support research which have been done by Balvers ( 1998) that is emission guarantor reputation and auditor reputation have an effect on negativity significance to initial return. Value of significance T for the emission guarantor reputation is 0.044 meaning significance at ? = 5%. Result of examination of this corellation indicate that emission guarantor reputation variable can explain initial return -0.306 or equal to 30.6% negative to initial return. Result of this research support research done by Carter and Dark ( 1992) that emission guarantor reputation, procentage share tender, old age company have an effect on negativity significance to initial return.